The Influences of Machine Translation Dependency on Translation Skill - Jorge August Valdano Reidina; Siti Fatimah Yuliani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
To translate one language to another language, sometimes some students still have difficulty translating foreign language due to their inexperience in the foreign language. This research uses a case study research design with a qualitative approach suitable for the terms and conditions with case study research design. The research conducted a pre-test and post-test translation test, which involved five subjects with two abstracts for each subject. This study showed that subjects were influenced by machine translation dependency on behavioral and result aspects. This study also showed the results differences, which showed that subjects had lower results when translated manually than translated used machine translation. Machine translation could help the students in translation tasks. However, dependency behavior could influence the progress and results of translation because it still has weaknesses in machine translation. The study advises users to use machine translation wisely to keep the advantages of machine translation and to decrease the disadvantages of machine translation.